Structural Analysis and Conduction Mechanisms in Polycrystalline Zinc Hydroxide Nitrate - Ruiz Madronero, Christhy; et al. (Inorganic Chemistry, 2018)
The conduction and dielectric properties in zinc hydroxide nitrate (Z5HN) were studied in detail as a function of the temperature and relative humidity by impedance spectroscopy, and the structure was investigated by X-ray diffraction (XRD). Elemental analysis indicated a layered material containing carbonate anions [Zn5(OH)8(NO3)1.6(CO3)0.2·1.7H2O] due to the high capability of adsorption of Z5HN, which makes this material appropriate for applications in real conditions. The water content affected the interlayer distance, conductivity, and dielectric response of the layered material. An electrostatic repulsive interaction after reduction of the water content as a function of the temperature causes an increase of the interlayer distance and a decrease in the conductivity response and dielectric behavior. The highest conductivity, 10−7 Ω−1 cm−1 , was obtained at a shorter interlayer distance for the sample heat-treated at 25 °C. The Z5HN synthesized was also characterized at different temperatures using thermogravimetric analysis and Fourier transform infrared and Raman spectroscopy. Multipeak analysis of the XRD patterns at various relative humidity levels showed the formation of a most hydrated phase and an increase of the interlayer distance related with the adsorption of water molecules. This layered material presented a conductivity of 10−5 Ω−1 cm−1 at high relative humidity (92%). The dipole−dipole interaction appeared to be the dominant mechanism for the dielectric behavior at the lowest temperatures and highest humidity due to the high water content in the Z5HN structure. Taking into account its crystallization water and high adsorption of water molecules in the interlayer region, a conduction pathway in the Z5HN structure was proposed, which provides the route for proton transport by hydrogen-bonding networks on the basis of a Grotthuss-type mechanism in facilitating the long-range proton hopping at 25 °C. The results for high relative humidity imply that a vehicular conduction mechanism also may contribute to the electrical response.<br